Timely adaptation of a Pediatric Unit to COVID-19 emergency in Northern Italy: the experience of Fondazione IRCCS Policlinico San Matteo in Pavia. - Novelli, Viola; Cutti, Sara; Muzzi, Alba; Marena, Carlo; Grugnetti, Giuseppina; Triarico, Antonio; Nicora, Carlo; Venturi, Alessandro; Licari, Amelia; Marseglia, Gian Luigi; Bossi, Grazia; Brambilla, Ilaria; et al. (Acta Biomedica Atenei Parmensis, 2020)
Italy is one of the most exposed countries worldwide to COVID-19, and Lombardy is the most affected region in Italy. In this context, Fondazione IRCCS Policlinico San Matteo in Pavia, one of the largest University hospitals in the region, has been involved in the management of the outbreak since its inception. Immediately after the communication of the first Italian COVID-19+ patient, the Pediatric Unit has been completely reorganized to face the approaching outbreak. The optimization of the Pediatric Unit resources for COVID-19 emergency is reported as an example to safely preserve health activity during the pandemic.